2018
DOI: 10.1007/s10096-018-3303-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of active Schistosoma infection in travellers and migrants using the ultra-sensitive in-house lateral flow test for detection of circulating anodic antigen (CAA) in serum

Abstract: Schistosomiasis is a parasitic disease affecting over 250 million people in the tropics. In non-endemic regions, imported Schistosoma infections are commonly diagnosed by serology, but based on antibody detection an active infection cannot be distinguished from a cured infection and it may take more than 8 weeks after exposure before seroconversion occurs. In endemic populations, excellent results have been described in diagnosing low-grade active Schistosoma infections by the detection of the adult worm-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…However, more recent clinical studies using the more sensitive UCP-LF CAA test indicated active infections in travelers with CAA serum levels even less than 1 pg/ mL. 11,15 We speculate that when infection intensities are very low, variation in CAA levels may be observed; circadian rhythms and feeding patterns as well as immune-mediated clearance mechanisms of the host may play a role. Current thinking is that a single worm pair might produce a minimum CAA level of 1 pg/mL serum (unpublished).…”
Section: Serum Assay Improvementsmentioning
confidence: 91%
“…However, more recent clinical studies using the more sensitive UCP-LF CAA test indicated active infections in travelers with CAA serum levels even less than 1 pg/ mL. 11,15 We speculate that when infection intensities are very low, variation in CAA levels may be observed; circadian rhythms and feeding patterns as well as immune-mediated clearance mechanisms of the host may play a role. Current thinking is that a single worm pair might produce a minimum CAA level of 1 pg/mL serum (unpublished).…”
Section: Serum Assay Improvementsmentioning
confidence: 91%
“…In contrast to the detection of eggs and circulating worm antigens, the presence of host antibodies against Schistosoma derived biomolecules is not necessarily a measure for ongoing active infection, except in those who would not previously have been exposed to Schistosoma parasites [i.e., individuals from non-endemic settings or travelers; ( 46 )]. In the current small endemic cohort, antibody detection in urine could not contribute to resolving disputes regarding anodic antigen negatives and cathodic antigen positives or indecisive/trace results as the analytical sensitivity of the assay was not sufficient to identify all infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…CAA-based lateral flow assays combined with up-converting phosphor reporter technology, work for both S. mansoni and S. haematobium . However, they have not as yet proven as effective with other schistosome species [ 20 , 21 , 22 ]. As a result, DNA, especially PCR-based parasite DNA detection assays, have stimulated much interest as alternative options due to their proven diagnostic accuracy, higher sensitivity, and wider range of applicability, including the ability to detect early pre-patent infections.…”
Section: A General Overview Of Diagnostics For Schistosomiasismentioning
confidence: 99%